From Silicon to Sunlight: Exploring the Evolution of Solar Cell Materials - Ashif Mohammad; Farhana Mahjabeen (JURIHUM : Jurnal Inovasi dan Humaniora, 2023)
Examines the development and evolution of solar cell materials with a focus on how these changes have affected solar energy conversion's effectiveness, stability, and scalability. The heading "From Silicon to Sunlight: Exploring the Evolution of Solar Cell Materials," among others. The chapters include "Perovskite Revolution: A Game-Changer in Solar Cell Technology," "Quantum Dots: Exploring Nanostructures for Efficient Solar Energy Conversion," "Tandem Solar Cells: Combining Materials for Enhanced Performance," "Stability Challenges: Addressing the Durability of Solar Cell Materials," "Emerging Trends: Materials Innovations for Next-Generation Solar Cells," and "Conclusion: Charting the Future Path of Solar Cell Materials." The transition away from silicon-based solar cells to substitute materials, like perovskites and quantum dots, and their potential for better light absorption and charge transport, are highlighted in the first part. The details of each material's unique characteristics, difficulties, and prospective uses are covered in the following sections. Quantum dots offer broad-spectrum absorption and improved charge transport features, whereas perovskite solar cells have excellent efficiency, solution process ability, and variable band gaps. Tandem solar cells mix different materials to increase efficiency and catch a wider range of sunlight. Encapsulation techniques, protective coatings, and improved material designs are used to handle stability concerns such moisture intrusion, UV degradation, and mechanical stressors. The review paper emphasizes the newest developments in solar cell technology, such as the use of abundant, sustainable materials, the creation of flexible solar cells, the incorporation of nanomaterial, and the investigation of cutting-edge characterization methods. Higher energy conversion efficiencies, enhanced sustainability, better flexibility, and the incorporation of solar cells into the built environment are just a few of the potential effects of these trends that could affect the use of solar energy in the future that are explored. The advancement of solar cell technology will be fueled by ongoing research and collaboration in materials science and engineering. The abstract underlines the significance of material innovation in determining the future of solar energy while summarizing the main conclusions of the review study.